The Modern Anti-Palamism and the Orthodox Doctrine of Theosis - Karavaltchev, Ventsislav (Forum Theologicum Sardicense, 2025)
Ventzislav Karavaltchev, The Modern Anti-Palamism and the Orthodox Doctrine of Theosis. The main theses of famous modern Orthodox theologians are considered in a polemical spirit, for whom the teaching of St. Gregory Palamas on the substance and energies of God is a major obstacle in the dialogue with the Western Church. An overview of the doctrine of deification developed in the Orthodox Church before the Great Schism is given, showing the authentic Christian character of the teaching of St. Gregory Palamas and the insolvency of modern criticism.